Anisotropy in the carbon monoxide (CO) line emission across the Milky Way’s disk - Soler, Juan D.; Heyer, M.; Benedettini, M.; Elia, D.; Hennebelle, P.; Klessen, Ralf S.; Girichidis, Philipp; Mininni, C.; Nucara, A.; Pelkonen, V.-M.; Molinari, S.; Smith, R. J.; et al. (Astronomy and astrophysics, 2025)
We present a study of the CO line emission anisotropy across the Milky Way’s disk to examine the effect of stellar feedback and Galactic dynamics on the distribution of the dense interstellar medium. We used the Hessian matrix method to characterize the 12CO(1-0) line emission distribution and identify the preferential orientation across line-of-sight velocity channels in the Dame et al. (2001, ApJ, 547, 792) composite Galactic plane survey, which covers the Galactic latitude range |b| < 5°. The structures sampled with this tracer are predominantly parallel to the Galactic plane toward the inner Galaxy, in clear contrast to the predominantly perpendicular orientation of the structures traced by neutral atomic hydrogen (HI) emission toward the same regions. The analysis of the Galactic plane portions sampled at higher angular resolution with other surveys reveals that the alignment with the Galactic plane is also prevalent at smaller scales. We find no preferential orientation in the CO emission toward the outer Galaxy, in contrast to the preferential alignment with the Galactic plane displayed by HI in that portion of the Milky Way. We interpret these results as the combined effect of the decrease in midplane pressure with increasing Galactocentric radius and SN feedback, which lifts diffuse gas more efficiently than dense gas off the Galactic plane.
Online veröffentlicht: 15. Dezember 2025
Gesehen am 19.02.2026